2009
DOI: 10.1016/j.pain.2009.07.010
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of adverse events in placebo groups of anti-migraine clinical trials

Abstract: In analgesic clinical trials, adverse events are reported for the painkiller under evaluation and compared with adverse events in the placebo group. Interestingly, patients who receive the placebo often report a high frequency of adverse events, but little is understood about the nature of these negative effects. In the present study, we compared the rates of adverse events reported in the placebo arms of clinical trials for three classes of anti-migraine drugs: NSAIDs, triptans and anticonvulsants. We identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
173
0
7

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 210 publications
(191 citation statements)
references
References 16 publications
11
173
0
7
Order By: Relevance
“…26 Previously published systematic reviews focused on the efficacy of specific drugs rather than comparative effectiveness and tolerability of all pharmacologic options. 27,28 In addition, the Institute of Medicine recommends basing treatment decisions on post-marketing studies tracking drug benefits and harms after FDA approval. [29][30][31] Thus, we conducted a systematic literature review of the comparative effectiveness and tolerability of the available preventive medications for episodic migraine in adults in outpatient settings to inform treatment and policy decisions (CRD42012001918).…”
Section: Introductionmentioning
confidence: 99%
“…26 Previously published systematic reviews focused on the efficacy of specific drugs rather than comparative effectiveness and tolerability of all pharmacologic options. 27,28 In addition, the Institute of Medicine recommends basing treatment decisions on post-marketing studies tracking drug benefits and harms after FDA approval. [29][30][31] Thus, we conducted a systematic literature review of the comparative effectiveness and tolerability of the available preventive medications for episodic migraine in adults in outpatient settings to inform treatment and policy decisions (CRD42012001918).…”
Section: Introductionmentioning
confidence: 99%
“…[30][31][32] Amanzio et al performed a systematic review of adverse effects of anti-migraine randomized placebo-controlled clinical trials. 32 The final sample consisted of 69 studies including 56 trials for triptans, 9 trials for anticonvulsants, and 8 trials for nonsteroidal anti-inflammatory drugs. The researchers found a high rate of adverse events in the placebo arms of trials, with the effects noted after taking antimigraine drugs matching those described for real drugs.…”
mentioning
confidence: 99%
“…For example, anticonvulsant placebos produced anorexia, memory difficulties, paresthesia and upper respiratory tract infections -all of which were adverse events reported in the side effect profile of the three classes of antimigraine drugs. 32 The linkage between reported side effects in the placebo groups and the known side effects of particular drugs suggests genuine nocebo effects that arose from the informed consent process.…”
mentioning
confidence: 99%
“…Importantly, however, the negative information completely abolished the effect of the analgesic treatment, thereby showing that negative expectations may block the efficacy of a welldocumented analgesic treatment. In line with this, a systematic review showed a high incidence of adverse events in placebo treated groups of anti-migraine clinical trials (Amanzio, Corazzini, Vase & Benedetti 2009). Noteworthy, the adverse events experienced in different placebo arms corresponded to the adverse events produced by the actual drug against which the placebo was compared.…”
Section: Awareness Of Placebo Components Is Critical In Clinical Pracmentioning
confidence: 68%
“…Studies investigating how patients' negative perception and expectations towards treatment contribute to treatment outcomes are also emerging (Amanzio, Corazzini, Vase & Benedetti 2009;Bingel et al 2011;Rief, Avorn & Barsky 2006).…”
Section: Awareness Of Placebo Components Is Critical In Clinical Pracmentioning
confidence: 99%